Multimodality Imaging in Valvular Structural Interventions - Karine Grigoryan; Camelia Demetrescu; Ioannis Kasouridis; Olukayode Abiola; Pier Giorgio Masci; Didem Oguz; Giulia Benedetti; Sze Mun Mak; Purvi Parwani; Rebecca Preston; Amedeo Chiribiri; Jane Hancock; et al. (Cardiac Failure Review)
Structural valvular interventions have skyrocketed in the past decade with new devices becoming available and indications for patients who would previously have been deemed inoperable. Furthermore, while echocardiography is the main imaging tool and the first line for patient screening, cardiac magnetic resonance and CT are now essential tools in pre-planning and post-procedural follow-up. This review aims to address imaging modalities and their scope in aortic, mitral and tricuspid structural valvular interventions, including multimodality imaging. Pulmonary valve procedures, which are mostly carried out in patients with congenital problems, are discussed. This article presents a guide on individualised imaging approaches on each of the available interventional procedures.